[Generics ; Biglang liko ; Film making [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1989)
Discusses the issues and implementation of Generic Act; the motels as pleasure point for lovers and film making as an art. Also includes interviews with Peque Gallaga on his film directing.
Generics (15 min.) -- Biglang liko (13 min.) -- Film making (17 min.)
VHS.
Some parts in Biglang liko have distorted sound.
Keywords: Gallaga, Peque -- Interviews; Drugs -- Generic substitution. -- Philippines; Cinematography; Drugs -- Laws and legislation -- Philippines; Motels -- Philippines; Motion pictures -- Production and direction. -- Philippines; Pharmaceutical policy -- Philippines